Impact of the local microstructure fluctuations on radiation-induced segregation in dilute Fe-Ni and Ni-Ti model alloys: A combined modeling and experimental analysis. (15th February 2022) - Huang, Liangzhao; Ma, Kan; Belkacemi, Lisa T.; Loyer-Prost, Marie; Meslin, Estelle; Toijer, Elin; Messina, Luca; Domain, Christophe; Vidal, Julien; Nastar, Maylise
Graphical abstract: Abstract: From a systematic atom probe tomography (APT) characterization of the radiation-induced segregation (RIS) in dilute Fe-Ni and Ni-Ti model alloys, we highlight fluctuations of the solute local concentration up to the scale of the APT specimens. We deduce the RIS at dislocation loops from a solute diffusion equation, that is solved at steady state, within the Voronoi's volume occupied by a single loop. From a statistical sampling of the Voronoi's volume and the dislocation loop radius modeled after the characterization of the microstructure by transmission electron microscopy, we provide the full RIS distribution. The present statistical approach of RIS demonstrates that the fluctuation of local solute concentrations in Fe-Ni and Ni-Ti mainly results from the dispersion in size and density of the dislocation loop population. Besides, we highlight the impact of the post-treatment parameters used in the APT protocol on the extracted RIS profiles. In Ni-Ti alloys, the simulated Ti-depletion profiles are in very good agreement with the measured ones. Furthermore, the dispersion of the loop radius and density is shown to play a critical role on the fluctuations of the Ti local concentration. In Fe-Ni, the identification of discrepancies between the simulated Ni-enrichment profiles and the measured ones provides a signature of additional operating mechanisms of the solute redistribution, such as radiation-induced precipitation.